(untitled) (Pulse, 2014)
Background Rapid diagnosis and timely initiation of effective therapy are the major challenges in intensive care units (ICUs) despite the advances in critical care medicine. Procalcitonin (PCT) is an innovative valuable laboratory marker in this regard. Objectives This study was undertaken to introduce PCT as a routine tool in regional hospitals by evaluating the utility of PCT in early diagnosis as well as in assessment of severity in septic patients in comparison to the traditional methods and inflammatory markers like cultures and C-reactive Protein (CRP). Method & Materials PCT and CRP were simultaneously measured in 73 medico-surgical ICU patients. The results of PCT, CRP and microbiological cultures were compared according to the five categories of PCT concentrations and the American College of Chest Physicians (ACCP) criteria based study groups. Results The clinical presentation of 75.3 % cases revealed a range of systemic inflammatory responses (SIRS). The diagnostic accuracy of PCT was higher (75.34%) with greater specificity (72.2 %), sensitivity (76.36%), positive and negative predictive values (89.36 % and 50%), positive likelihood ratio (2.75) as well as the smaller negative likelihood ratio (0.33). Both serum PCT and CRP values in cases with sepsis, severe sepsis and septic shock were significantly higher from that of the cases with SIRS and no SIRS (p< 0.01). Conclusion The diagnostic utility of both PCT and CRP are close yet PCT is found to be superior to that of CRP or microbiological culture in terms of accuracy in identification of patients with sepsis and to assess the severity of sepsis as well DOI: http://dx.doi.org/10.3329/pulse.v5i2.20259 Pulse Vol.5 July 2011 p.5-15